Photoluminescence and Refractive Index Dispersion Properties of Zn3−xMx(PO4)2 (M=Co, Ni; x = 1) Nanoparticles - Youssef El azizi; Hayat Salhi; Assaad Elouafi; Abdeslam Tizliouine; Sara Ezairi (Engineering Proceedings, 2024)
This study investigated the structural, optical, and photoluminescence properties of Zn3−xMx(PO4)2 (M=Co, Ni; x = 1) nanoparticles, synthesized via the solid-state method. The optical constants and dispersion energy parameters were determined using UV–visible spectroscopy. The optical band gaps were found to be 2.48 eV for Zn3(PO4)2, 3.05 eV for Zn2Ni(PO4)2, and 3.12 eV for Zn2Co(PO4)2. The optical dielectric constant of Zn3−xMx(PO4)2 (M=Co, Ni; x = 1) was also determined. Photoluminescence spectra revealed peaks at 2.56 eV for Zn3(PO4)2, 3.26 eV for Zn2Co(PO4)2, and 2.47 eV for Zn2Ni(PO4)2. These peaks correspond to the recombination of excitons and/or shallowly trapped electron–hole pairs, indicating band-edge emission.